Menjawab Kerancuan Kurikulum 2013 pada Mapel Bahasa Arab di Madrasah - Zamroni, Ahmad (At- Ta'lim : Jurnal Pendidikan, 2017)
Curriculum 2013 that implemented in Indonesia is very influence on the sustainability of learning at the school, especially the Arabic language. This paper attempts to analyze the Arabic language learning in the curriculum 2013 as an evaluation and revision of the content standards and instructional materials Arabic language books published by the Ministry of Religious Affairs. The result shows that the standard content of Arabic lesson has a problem in mapping of domain knowledge and skills, the lesson material also never tested and researched. This had an impact on the effectiveness of Arabic learning in the classroom.